2012
DOI: 10.1177/0748233712469646
|View full text |Cite
|
Sign up to set email alerts
|

Induction of vitellogenin synthesis in immature male yellowfin seabream (Acanthopagrus latus) exposed to 4-nonylphenol and 17β-estradiol

Abstract: In the present study, the effects of xenoestrogen 4-nonylphenol (4-NP) and 17β-estradiol (E2) on the synthesis of vitellogenin (VTG) in immature male yellowfin seabream (Acanthoparus latus) were assessed to determine the potential use of this species as a biological model for studying endocrine disrupters in the Musa estuary in southern seawaters of Iran. A total number of 104 fish were injected by 10, 50, 100, 150 and 200 µg g(-) (1) week(-) (1) of 4-NP and 2 µg g(-) (1) week(-) (1) of E2, and their blood pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…The plasma biochemical constituents, thyroid hormones, liver function enzymes and ionoregulatory endpoints could also be used as biomarkers to reflect the toxicity of chemicals as they have been frequently used for the toxicity assessment of other PAHs in fish and other animals (Alonso-Alvarez et al, 2007;Kim et al, 2008;Latif et al, 2014;Maria et al, 2002;Okwu et al, 2014;Osman et al, 2009;Salman, 2011;Tintos et al, 2008;Wegwu and Omeodu, 2010). Plasma biochemical indicators and transaminases have been proved to be suitable stress biomarkers in fish because they are inexpensive, less variable, more highly conserved between species and are easy to measure (Naderi et al, 2015;Senthil Kumaran et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The plasma biochemical constituents, thyroid hormones, liver function enzymes and ionoregulatory endpoints could also be used as biomarkers to reflect the toxicity of chemicals as they have been frequently used for the toxicity assessment of other PAHs in fish and other animals (Alonso-Alvarez et al, 2007;Kim et al, 2008;Latif et al, 2014;Maria et al, 2002;Okwu et al, 2014;Osman et al, 2009;Salman, 2011;Tintos et al, 2008;Wegwu and Omeodu, 2010). Plasma biochemical indicators and transaminases have been proved to be suitable stress biomarkers in fish because they are inexpensive, less variable, more highly conserved between species and are easy to measure (Naderi et al, 2015;Senthil Kumaran et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have indicated that HSI is an unspecific biomarker to indicate the harmful effects of EDCs (Ishibashi et al, 2006;Kumari et al, 2014;Verslycke et al, 2002). It has also been documented that estrogenic EDCs caused increases in HSI by the alternation of liver VTG production in fish (Feifarek, 2015;Naderi et al, 2015). The liver VTG production can lead to hypertrophy of hepatocytes (Arukwe and Goksøyr, 1998;Zha et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…According to an investigation, the structure of NP is similar to 17β-estradiol (E2), and NP can compete to inhibit the combination of E2 with the estrogen receptor (ER) of the target organ [ 44 , 45 ]. It has been reported that E2 could increase the 5-HT level in the nervous system by inhibiting the MAO activity [ 8 , 46 ].…”
Section: Discussionmentioning
confidence: 99%